Effects of montelukast compared to double dose budesonide on airway inflammation and asthma control. - Barnes, N; Laviolette, M; Allen, D; Flood-Page, P; Hargreave, F; Corris, P; O'Connor, B; Tate, H; Parker, D; Pavord, I (2007)
Many patients with asthma remain symptomatic with impaired airway function on inhaled steroids. This study investigates the relationship between the clinical effect seen in response to additional treatment and the effect on airway inflammatory indices. Seventy-five adult asthmatic patients, incompletely controlled on 800 mcg budesonide/day, were randomised following a 4 week run-in period, to a double-blind, multi-centre controlled clinical trial of doubling inhaled corticosteroid (budesonide 1600 mcg/day) or adding 10mg montelukast for 12 weeks. Induced sputum was collected at baseline and end of treatment and analysed for eosinophil and neutrophil percentages, leukotrienes C4, D4 and E4, IL-8, Eosinophil Cationic Protein (ECP) and histamine. Sputum evidence of inflammation (2.0% eosinophils) was seen in only 29% of these patients and the percentage of eosinophils and other markers of airway inflammation did not change over the study period in either treatment group. There were significant improvements in am PEF (montelukast: 31.7 L/min, budesonide: 32.3 L/min) and quality of life with both treatments. We conclude that while both treatments showed similar improvements in lung function and quality of life, there was no evidence from these sputum markers measured that the effects were mediated via a reduction in airway inflammation or that the level of pre-treatment markers was associated with outcome.